Anti-static hard coating and preparation method thereof

By adopting a hard coating with a multi-layer structure in the semiconductor industry, including a metal transition layer, a metal carbide layer and a dual-doped layer, the existing materials have solved the problems of unstable resistance value, insufficient chemical and thermal stability, and poor wear resistance in anti-static materials, and achieved moderate electrostatic resistance and excellent corrosion resistance, low friction coefficient and high wear resistance, extending service life.

CN119800278APending Publication Date: 2025-04-11GUANGDONG UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411970109.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In terms of anti-static electricity, existing materials have problems such as unstable resistance values, insufficient chemical and thermal stability, and poor wear resistance, which is difficult to meet the strict requirements of the semiconductor industry for electrostatic impedance.

Method used

A hard coating with a multi-layer structure, including a metal transition layer, a metal carbide layer and a bi-doped layer, is deposition through high-power pulse magnetron sputtering technology to design moderate electrostatic impedance, excellent corrosion resistance, low friction coefficient and high wear resistance.

Benefits of technology

It achieves moderate electrostatic impedance, excellent corrosion resistance, low friction coefficient and excellent wear resistance, improves the adaptability, bonding and bearing properties of the hard coating on different substrates, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800278A_ABST
    Figure CN119800278A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-static hard coating and a preparation method, the hard coating comprises a metal transition layer, a metal carbide layer and a binary doping layer, the metal transition layer is deposited on the surface of a matrix, and metal MA in the metal transition layer is one of Ti, Cr and Zr; the metal carbide layer is deposited on the surface of the metal transition layer, and the compound component of metal carbide is MAC; the double-element doped layer is deposited on the surface of the metal carbide layer, the compound component of the double-element doped layer is ta-C: MB / Si, and MB is one of Cu, Ag and Au. By designing the hard coating of a multi-element and multi-layer structure, the properties of moderate electrostatic impedance, excellent corrosion resistance, low friction coefficient, excellent wear resistance and the like are obtained, and the adaptability, binding force and bearing capacity of the hard coating on different matrixes are improved. The hard coating can be widely applied to the technical field of hard coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of hard coatings, and in particular to an antistatic hard coating and a preparation method thereof. Background Art

[0002] Static electricity is everywhere in our daily lives. Electrostatic discharge (ESD) can cause serious damage to the manufacturing process and operation of electronic products. There are two main types of damage. One is thermal failure caused by the heat generated by the current generated by electrostatic discharge, and the other is breakdown caused by excessive voltage induced by the accumulated charge of electrostatic discharge. In addition, ESD electrostatic discharge can easily interfere with electronic circuits. In semiconductor processes such as chip packaging, chips may be damaged by static electricity, affecting the yield. With the miniaturization of semiconductor components below 10 nanometers, their tolerance to static electricity is decreasing.

[0003] The existing materials currently used in the industry, such as anodized layers and Teflon coatings, have too high surface resistance values. For example, local static electricity is easily accumulated on the surface of the carrier or carrier. These accumulated static charges cannot be conducted away in time, which will lead to abnormal discharge scenes, thereby directly damaging expensive chips and microcircuits. In addition to the production and application environment, peripheral related test instruments, packaging, molds and other semiconductor components must have anti-static options. The semiconductor industry requires that the electrostatic impedance cannot be too high or too low, and the requirements are becoming more and more stringent, which is something that traditional coating materials cannot meet.

[0004] In addition, the semiconductor industry has very high cleanliness requirements for production equipment during the production process. Some equipment components such as jigs, carriers, carriers, guide rails, etc. are cleaned regularly. After heating and alkali washing, the traditional anodized layer and Teflon spray coating will peel off and can no longer guarantee the anti-static function. Therefore, the second pain point is generated, requiring the new anti-static coating material to have good chemical stability and thermal stability; and in the long-term continuous production process, the detection jig or equipment components will wear out. Increasing its wear resistance can reduce the replacement frequency and increase the service life of the components.

[0005] Therefore, in the semiconductor industry, the miniaturization of chips and electronic devices, the high speed of operating systems, and the use of factory automation technology have made ESD control systems an important factor in quality control and reliability assurance of semiconductor equipment components and devices. Traditional materials cannot dissipate static electricity, or traditional coatings are not resistant to high temperatures and chemical corrosion, or have poor mechanical properties, which affect product life and are receiving more and more attention. New technologies and new materials are urgently needed to solve these problems.

[0006] Existing diamond-like carbon-based thin film materials cannot be directly applied in the ESD field. The resistance value is low (103-105ohm / sq), which is lower than the industry standard (105-109ohm / sq); and the impedance is not stable enough. Under different film thicknesses and different workpiece surface roughness, the resistance value can fluctuate by up to three orders of magnitude. The chemical stability and thermal stability of existing diamond-like carbon-based thin film materials are not good enough. Under alkaline washing at around 100°C, the resistance value and film bonding strength cannot achieve long-term stability.

[0007] In summary, there is a strong market demand in the ESD application field to find an advanced material to replace traditional materials, so as to meet the above comprehensive performance requirements and solve the new pain points of the industry. Summary of the invention

[0008] In order to solve at least one of the above technical problems, the present application provides an antistatic hard coating and a preparation method, and the technical solution adopted is as follows.

[0009] The antistatic hard coating provided in the present application comprises a metal transition layer, a metal carbide layer and a binary doping layer, wherein the metal transition layer is deposited on the surface of the substrate, and the metal M in the metal transition layer is A is one of Ti, Cr, and Zr; the metal carbide layer is deposited on the surface of the metal transition layer, and the compound component of the metal carbide is M A C; the binary doping layer is deposited on the surface of the metal carbide layer, and the compound composition of the binary doping layer is ta-C: M B / Si,M B It is one of Cu, Ag and Au.

[0010] In some embodiments of the present application, the thickness of the metal transition layer is 0.1 to 0.2 μm.

[0011] In certain embodiments of the present application, the thickness of the metal carbide layer is 0.5 to 1 μm.

[0012] In some embodiments of the present application, the thickness of the binary doped layer is 1 to 2 μm.

[0013] In some embodiments of the present application, the C content in the binary doped layer is 80 to 90 at.%, and the Si content is 10 to 20 at.%. B The content is 2 to 5 at.%.

[0014] In some embodiments of the present application, the sp 3 The bond content is not less than 80%, the metal element M BIt is dissolved in the ta-C structure in a free state.

[0015] The preparation method provided in the present application is to deposit and obtain a hard coating, and the preparation method includes the following process flow:

[0016] loading a substrate into a reaction chamber;

[0017] The reaction chamber is evacuated and heated, and the substrate is ion cleaned;

[0018] Inert gas is introduced into the reaction chamber, a metal transition layer is deposited on the surface of the substrate, a metal carbide layer is deposited on the surface of the metal transition layer, and a binary doping layer is deposited on the surface of the metal carbide layer.

[0019] In some embodiments of the present application, the metal transition layer is deposited by high-power pulsed magnetron sputtering technology, and the current density of the metal target is 0.5 to 1 A / cm 2 , the bias voltage of the substrate is -100 to -150 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 5 to 10 min.

[0020] In some embodiments of the present application, the metal carbide layer is deposited by high power pulsed magnetron sputtering technology, and the current density of the graphite target is 1 to 1.5 A / cm 2 , the current density of the metal target is 0.5 to 1A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 30 to 60 min.

[0021] In some embodiments of the present application, when depositing the binary doped layer, a graphite target is sputtered by high-power pulsed magnetron sputtering technology, and the current density of the graphite target is 1 to 1.5 A / cm 2 The metal target and Si target were sputtered by bipolar pulsed magnetron sputtering technology. The current density of the metal target was 0.05 to 0.1 A / cm 2 , the current density of Si target is 0.2 to 0.4A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 60 to 120 min.

[0022] The present application has at least the following beneficial effects: in the present application, by designing a hard coating with a multi-layer structure, the present application obtains properties such as moderate electrostatic impedance, excellent corrosion resistance, low friction coefficient, and excellent wear resistance, thereby improving the adaptability, bonding force, and bearing capacity of the hard coating on different substrates. The present application can be widely used in the field of hard coating technology.

[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present application is further illustrated below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments embodied in the following drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0025] Figure 1 Schematic diagram of the structure of the hard coating in this application.

[0026] Figure 2 Schematic diagram of the interior of the reaction chamber.

[0027] Figure 3 The following are SEM images of the surface and cross section of the hard coating in this application.

[0028] Figure 4 The graph shows the nanohardness, wear rate and corrosion current of the hard coating in this application.

[0029] Figure 5 This is a curve diagram showing the relationship between the surface resistance value of the hard coating in this application and the surface CuSi atomic content. DETAILED DESCRIPTION

[0030] Combine the following Figures 1 to 5 The embodiments of the present application are described in detail, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.

[0031] In the description of the present application, it should be understood that the terms "center", "middle", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0032] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0033] In the description of this application, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example: it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0034] In the description of the present application, if there is a description with reference to the terms "one embodiment", "some embodiments", "an embodiment", "some examples", "some embodiments", "illustrative embodiment", "example", "specific example", "some examples", etc., it means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0035] The present application relates to an antistatic hard coating, which includes a metal transition layer, a metal carbide layer and a binary doping layer. The metal transition layer is deposited on the surface of a substrate, the metal carbide layer is deposited on the surface of the metal transition layer, and the binary doping layer is deposited on the surface of the metal carbide layer.

[0036] The hard coating in this application adopts a multi-layer structure design including a metal transition layer, a metal carbide layer and a binary doping layer to improve the adaptability, bonding force and bearing capacity of the hard coating on different substrates. The multi-layer structure design can obtain a semiconductor electrostatic dissipative coating with excellent antistatic properties, mechanical properties, friction and wear properties, and corrosion resistance.

[0037] In the metal transition layer, the metal element is a carbide-forming element. It should be noted that the carbide-forming element refers to an element that can react with carbon to form carbides. Specifically, M A It is one of Ti, Cr and Zr. These three elements have good corrosion resistance and can also have good bonding with the surface coating.

[0038] It should be noted that the compound composition of the metal carbide is M A C.

[0039] In the dual-doped layer, metal elements and Si co-doped ta-C layer, the compound composition is ta-C: M B / Si, the metal element is a non-carbide forming element. Among them, Si and C bond to form sp 3 Si-C bonds significantly increase sp 3 The stability of the carbon structure. Doping with non-carbide metal elements can adjust the resistance value of the hard coating to achieve the best static dissipation area. It should be noted that the ta-C structure is high SP 3 Diamond-like coatings with chemical bond content are called ta-C, which is tetrahedral amorphous carbon. Non-carbide-forming elements are elements that do not react with elemental carbon to form carbides in their natural straight state.

[0040] Specifically, M B It is one of Cu, Ag and Au. It should be noted that elements such as Cu, Ag and Au have stable chemical properties and do not react with carbon to form carbides. The doping of these elements can effectively reduce the internal stress of the coating.

[0041] In some embodiments, the thickness of the metal transition layer is 0.1 to 0.2 μm. It is understandable that the metal transition layer mainly plays a buffering role to improve the interface bonding strength; too thick or too thin will reduce the coating bonding strength, so the designed thickness is 0.1 to 0.2 μm.

[0042] In some embodiments, the thickness of the metal carbide layer is 0.5 to 1 μm. Since the metal transition layer and the binary doping layer have different hardness, physical properties, etc., the metal carbide layer is required to connect the binary doping layer and the metal transition layer to improve the bonding force between the metal transition layer and the binary doping layer. On the other hand, the metal carbide layer can also serve as a carrier of the binary doping layer. Too thick or too thin will reduce the carrying capacity.

[0043] In some embodiments, the thickness of the binary doped layer is 1 to 2 μm. As an outer functional layer, the binary doped layer needs a relatively high thickness to resist external corrosion. On the other hand, as an outer functional layer, the binary doped layer needs a certain thickness to resist wear. When the thickness is too small, it is not conducive to resisting wear; when the thickness is too large, the internal stress of the coating is large and the bonding force is poor.

[0044] In some embodiments, the C content in the binary doped layer is 80 to 90 at.%, the Si content is 10 to 20 at.%, and the M B The content is 2 to 5 at.%, wherein C is the main element of the binary doping layer. When the content of C is too low, sufficient CC SP cannot be formed.3 When the content of C is too high, the content of doping elements will be reduced, so that the doping elements cannot play their role. The addition of Si can improve the thermal stability of the coating and enhance the interface bonding strength. When the content of Si is too high, the hardness of the coating will be reduced. When the content of Si is too low, the thermal stability of the coating will be reduced. Metal element M B The addition of M plays a role in regulating the internal stress of the coating. B If the content is too low, the internal stress regulation effect of the coating is not obvious, and the resistance increases. B If the content is too high, the resistance will be too low.

[0045] In some embodiments, in the binary doped layer, the sp 3 The bond content is not less than 80%, due to sp 3 The high content of SP makes the hard coating have good wear resistance and corrosion resistance, which helps to extend the service life of the coating. 3 The bond can improve the hardness and corrosion resistance of the coating. If the content is less than 80%, the hardness of the coating will decrease and the corrosion resistance will decrease.

[0046] In some embodiments, in the binary doped layer, the metal element M B Dispersed and dissolved in the ta-C structure in a free state.

[0047] The present application relates to a preparation method, which deposits a hard coating. The prepared hard coating has an anti-static effect and is suitable for semiconductor fixtures, disks, carriers and guide rails based on materials such as stainless steel, aluminum alloy, titanium alloy, ceramic, and glass.

[0048] The preparation method includes the following process flow:

[0049] loading a substrate into a reaction chamber;

[0050] The reaction chamber is evacuated and heated, and the substrate is ion cleaned;

[0051] Inert gas is introduced into the reaction chamber, a metal transition layer is deposited on the surface of the substrate, a metal carbide layer is deposited on the surface of the metal transition layer, and a binary doping layer is deposited on the surface of the metal carbide layer.

[0052] It should be noted that the surfaces of the substrate, the metal transition layer, the metal carbide layer and the binary doping layer are all subjected to ion bombardment. During the ion bombardment, the output power of the ion source is 2 to 5 kW, the substrate bias voltage is -400 to -800 V, the gas pressure in the reaction chamber is 0.6 to 3 Pa, and the bombardment time is 20 to 30 min.

[0053] The metal transition layer is deposited by high-power pulsed magnetron sputtering technology, and the metal target is turned on. The current density of the metal target is 0.5 to 1A / cm 2 , the bias voltage of the substrate is -100 to -150 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 5 to 10 min.

[0054] The metal carbide layer is deposited by high-power pulsed magnetron sputtering technology, with the metal target and the graphite target turned on at the same time. The current density of the graphite target is 1 to 1.5A / cm 2 , the current density of the metal target is 0.5 to 1A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 30 to 60 min.

[0055] When depositing the dual-doped layer, the graphite target is sputtered by high-power pulsed magnetron sputtering technology (HIPIMS), and the metal target, graphite target and Si target are turned on at the same time. The current density of the graphite target is 1 to 1.5A / cm 2 The metal target and Si target were sputtered by bipolar pulsed magnetron sputtering (BPMS) with a current density of 0.05 to 0.1 A / cm 2 , the current density of Si target is 0.2 to 0.4A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 60 to 120 min.

[0056] In this application, the binary doped layer is prepared by sputtering using HIPIMS technology combined with BPMS technology, which can effectively avoid large particles and other growth defects caused by deposition technologies such as arc, obtain a smooth and dense binary doped layer, and improve the corrosion resistance of the hard coating.

[0057] The antistatic resistance value of the hard coating prepared in this application is 10 5 Up to 10 9 ohm / sq, the nano-hardness of the coating is greater than 5000HV, and the corrosion current density is less than 0.5*10 -6 A / cm 2 , the friction coefficient is 0.1 to 0.15, and the wear rate is less than 1*10 -8 mm / Nm. It can be understood that the hard coating has good wear resistance and corrosion resistance and can extend the service life.

[0058] The contents of the present application are described in detail below in conjunction with specific embodiments. It should be noted that the following description is only for illustrative purposes and is not a specific limitation to the present application.

[0059] Example 1

[0060] (1) Cleaning the substrate

[0061] The substrate is made of stainless steel and is cleaned with alcohol ultrasonic wave, then cleaned with ionized water and blown dry.

[0062] (2) Ion source bombards the substrate surface

[0063] Place the substrate into the reaction chamber and evacuate to 5*10 -3 Pa, and heated. 200 sccm of argon gas was introduced, and the gas pressure was 0.6 to 3 Pa. The ion source was turned on, the power of the ion source was 2 to 5 kW, the bias voltage of the substrate was -400 to -800 V, and the bombardment time was 20 to 30 min.

[0064] (3) Deposition of metal transition layer

[0065] The metal target is Ti target, the HIPIMS power supply is turned on, and the current density of the metal target is 0.8A / cm 2 , the bias voltage of the substrate is -100 V, the gas pressure of the reaction chamber is 0.5 Pa, and the deposition time is 10 min.

[0066] (4) Deposition of metal carbide layer

[0067] The metal target is Ti target, and the HIPIMS power supply is turned on. The current density of the graphite target is 1.2A / cm 2 , the current density of the metal target is 0.7A / cm 2 , the bias voltage of the substrate is -100 V, the gas pressure of the reaction chamber is 0.5 Pa, and the deposition time is 45 min.

[0068] (5) Deposition of dual doped layers

[0069] The metal target is a Cu target, and the graphite target is sputtered using HIPIMS technology. The current density of the graphite target is 1.2A / cm 2 BPMS technology was used to sputter metal targets and Si targets. The current density of the metal target was 0.07A / cm 2 , the current density of Si target is 0.3A / cm 2 , the substrate bias voltage is -100 V, the gas pressure in the reaction chamber is 0.5 Pa, and the deposition time is 90 min.

[0070] Example 2

[0071] The difference between Example 2 and Example 1 is that the metal element of the metal transition layer is Cr, and the metal element of the metal carbide layer is Cr.

[0072] Example 3

[0073] The difference between Example 3 and Example 1 is that the metal element of the metal transition layer is Zr, and the metal element of the metal carbide layer is Zr.

[0074] Example 4

[0075] The difference between Example 4 and Example 1 is that the metal element in the binary doping layer is Ag, and the compound structure is Ag / Si-ta-C.

[0076] Example 5

[0077] The difference between Example 5 and Example 1 is that the metal element in the binary doping layer is Au, and the compound structure is Au / Si-ta-C.

[0078] Example 6

[0079] The difference between Example 6 and Example 1 is that when depositing the dual-doped layer, the current density of the Si target is 0.2 A / cm 2 .

[0080] Example 7

[0081] The difference between Example 7 and Example 1 is that when depositing the binary doped layer, the current density of the Si target is 0.4 A / cm 2 .

[0082] Example 8

[0083] The difference between Example 8 and Example 1 is that when depositing the dual-doped layer, the current density of the Cu target is 0.1 A / cm 2 .

[0084] Example 9

[0085] The difference between Example 9 and Example 1 is that when depositing the dual-doped layer, the current density of the Cu target is 0.05 A / cm 2 .

[0086] Comparative Example 1

[0087] (1) Cleaning the substrate

[0088] The substrate is made of stainless steel and is cleaned with alcohol ultrasonic wave, then cleaned with ionized water and blown dry.

[0089] (2) Ion source bombards the substrate surface

[0090] Place the substrate into the reaction chamber and evacuate to 5*10 -3 Pa, and heated. 200 sccm of argon gas was introduced, and the gas pressure was 0.6 to 3 Pa. The ion source was turned on, the power of the ion source was 2 to 5 kW, the bias voltage of the substrate was -400 to -800 V, and the bombardment time was 20 to 30 min.

[0091] (3) Deposition of metal transition layer

[0092] The metal target is Ti target, the HIPIMS power supply is turned on, and the current density of the metal target is 0.8A / cm 2 , the bias voltage of the substrate is -100 V, the gas pressure of the reaction chamber is 0.5 Pa, and the deposition time is 10 min.

[0093] (4) Deposition of metal carbide layer

[0094] The metal target is Ti target, and the HIPIMS power supply is turned on. The current density of the graphite target is 1.2A / cm 2 , the current density of the metal target is 0.7A / cm 2 , the bias voltage of the substrate is -100 V, the gas pressure of the reaction chamber is 0.5 Pa, and the deposition time is 45 min.

[0095] (5) Deposition of surface ta-C layer

[0096] The graphite target was sputtered using HIPIMS technology, and the current density of the graphite target was 1.2A / cm 2 , the substrate bias voltage is -100 V, the gas pressure in the reaction chamber is 0.5 Pa, and the deposition time is 90 min.

[0097] Comparative Example 2

[0098] The difference between Comparative Example 2 and Comparative Example 1 is that when depositing the surface ta-C layer, the Si target is sputtered by BPMS technology, and the Si is doped. The current density of the Si target is 0.3A / cm 2 .

[0099] Comparative Example 3

[0100] The difference between Comparative Example 3 and Comparative Example 1 is that when depositing the surface ta-C layer, the Cu target is sputtered by BPMS technology, doped with Cu, and the current density of the Cu target is 0.07A / cm 2 .

[0101] Comparative Example 4

[0102] The difference between Comparative Example 4 and Comparative Example 1 is that when depositing the surface ta-C layer, the Cu target and the Si target are sputtered by BPMS technology, and Cu and Si are doped. The current density of the Cu target is 0.07A / cm 2 , the current density of Si target is 0.42A / cm 2 .

[0103] Comparative Example 5

[0104] The difference between Comparative Example 5 and Comparative Example 1 is that when depositing the surface ta-C layer, the Cu target and the Si target are sputtered by BPMS technology, and Cu and Si are doped. The current density of the Cu target is 0.07A / cm 2 , the current density of Si target is 0.18A / cm 2 .

[0105] Comparative Example 6

[0106] The difference between Comparative Example 6 and Comparative Example 1 is that when depositing the surface ta-C layer, the Cu target and the Si target are sputtered by BPMS technology, and Cu and Si are doped. The current density of the Cu target is 0.02A / cm 2 , the current density of Si target is 0.18A / cm 2 .

[0107] Comparative Example 7

[0108] The difference between Comparative Example 7 and Comparative Example 1 is that when depositing the surface ta-C layer, the Cu target and the Si target are sputtered by BPMS technology, and Cu and Si are doped. The current density of the Cu target is 0.012A / cm 2 , the current density of Si target is 0.18A / cm 2 .

[0109] Table 1, Parameter comparison of the hard coatings prepared in each embodiment and each comparative example

[0110]

[0111]

[0112] The following is an analysis of the data in Table 1.

[0113] Examples 1, 2, and 3 correspond to different metal transition layers and metal doping layers respectively; among the three, Example 1 corresponding to Ti metal has the lowest resistance, and Example 3 corresponding to metal Zr has the lowest corrosion current density. In addition, there is little difference in hardness, wear rate, and high temperature stability, which is due to the consistency of the surface coating and its performance is mainly affected by the surface layer.

[0114] Examples 4 and 5 correspond to different metal binary doping layers (Ag and Au), respectively. Compared with the two, Example 4 corresponding to Ag has relatively low resistance and relatively high hardness; while Example 5 corresponding to Au has relatively low wear rate.

[0115] Examples 6 and 7 correspond to doping powers with different Si element contents, and different doping powers lead to different contents. The current density of the Si target is 0.2A / cm 2The corresponding embodiment 6 has relatively poor thermal stability and relatively low hardness; the current density of the Si target is 0.4A / cm 2 The corresponding embodiment 7 has relatively high thermal stability, and also has relatively high resistance and hardness.

[0116] Examples 8 and 9 correspond to different copper doping powers. 0.1A / cm 2 The sputtering current density of Example 8 corresponding to 0.05A / cm 2 Example 9 of the sputtering current density has relatively high resistance and relatively low corrosion current density.

[0117] Comparative Example 1 uses HIPIMS technology to prepare the surface ta-C coating, which has the highest resistance, the greatest hardness and the lowest corrosion current density.

[0118] Comparative Example 2 uses BPMS technology to prepare Si-doped ta-C coating, which has a larger resistance of 135.6 (107 ohms), the highest thermal stability, higher hardness and lower corrosion current density.

[0119] Comparative Example 3 uses BOMS to prepare a Cu-doped ta-C coating, which has lower resistance but poor thermal stability and also has a hardness of 6847 Hv.

[0120] Comparative Examples 4 and 5: Cu and Si are doped simultaneously, and the current density of the Cu target is 0.07 A / cm 2 , the current density of Si target is different to prepare Si coatings with different Si contents. When the current density of Si target is 0.42A / cm 2 The corresponding comparative example 4 has a relatively high resistance value, good thermal stability, high hardness and relatively low corrosion current density; when the current density of the Si target is 0.18A / cm 2 When , the corresponding comparative example 5 has relatively low resistance and relatively high thermal stability.

[0121] Comparative Examples 6 and 7 are for doping Cu and Si simultaneously, and the current density of Si target is 0.18A / cm 2 , to prepare coatings with different Cu contents. When the current density of the Cu target is 0.02A / cm 2 When the Cu target has a relatively high resistance and a high wear rate, the current density is 0.012A / cm 2 When it is used, it has relatively low resistance and relatively low wear rate.

[0122] The following is an analysis and explanation of the contents of each figure.

[0123] Figure 3This is a SEM image of the surface and interface of Example 4. The dual-doped layer in the image has a dense structure.

[0124] Figure a is the surface morphology of the antistatic coating, where the typical cauliflower-like cluster structure of the amorphous carbon series coating can be seen.

[0125] Figure b is the cross-sectional morphology of Example 4. The coating structure is composed of a metal Ti transition layer, a metal carbide layer, and a binary doping layer. The cross-section of the surface binary doping layer has no obvious crystal structure, a dense structure, and good corrosion resistance, which is due to the fact that the main body of the coating is amorphous carbon.

[0126] Figure 4 a, b, and c are the resistance, hardness, and corrosion current density of Examples 1 and 4 and Comparative Examples 1 and 6 for four hours at constant potential. In Figure a, the metal elements in the transition layer and metal carbide of Examples 1 and 4 are different. The resistance of Example 1 is less than that of Example 4 because the resistivity of Ti is lower than that of Cr. The resistance values ​​of Comparative Examples 1 and 6 are 146.3·10 7 ohms, 26.7·10 7 ohms. As shown in Figure a, element doping can reduce the coating resistance. In addition, compared with metal element and Si element doping, metal element doping can significantly reduce the coating resistance. This is because element doping reduces the SP in the coating. 3 In addition, since the conductivity of elemental Si is lower than that of metal elements, the resistance of Si-doped coatings is higher than that of metal-doped coatings.

[0127] Figure b shows the corresponding hardness, which is 2.4845·10 -9 mm 3 / N·m、3.6178·10 -9 mm 3 / N·m, 2.7519·10 -9 mm 3 / N·m、3.1161·10 -9 mm 3 / N·m. As shown in Figure b, element doping can reduce the wear rate of the coating. This is because element doping reduces the SP 3 Bond content, resulting in SP 2 As the bond content increases, more graphite phase structures are formed, which has a self-lubricating effect. In addition, the metal Cu element also has a self-lubricating effect, which can reduce the friction coefficient and reduce the wear rate.

[0128] Figure c is the corresponding constant potential corrosion current density curve over time. The corresponding corrosion current density in the last 5 minutes is 24.9·10 -8 A / cm 2 、23.7·10 -8A / cm 2 、15.3·10 -8 A / cm 2 , 22.7·10 -8 A / cm 2 As shown in Figure c, all four groups of cases in the figure show excellent corrosion resistance, but the lower the corrosion current density, the better the corrosion resistance of the coating. From the comparison of the curves in the figure, it can be seen that metal element doping and Si doping have worse corrosion resistance than non-doping, which is due to the reduction of the SP3 bond content in the coating.

[0129] Figure 5 The resistance curve of Cu and Si in the dual-doped layer increases with the increase of their content. The coating resistance decreases with the decrease of the doping content. Element doping can reduce the coating resistance, and the resistance decreases more significantly with the increase of the doping content. This is because element doping reduces the SP in the coating. 3 Bond content, SP in coating 2 The more graphite phases in the structure, the lower the resistance; in addition, since the conductivity of elemental Si is lower than that of metal elements, the resistance of Si-doped coatings is higher than that of metal-doped coatings.

[0130] The above is a detailed description of the implementation methods of the present application in conjunction with the accompanying drawings, but the present application is not limited to the above implementation methods. Various changes can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. An antistatic hard coating, characterized in that: include The metal transition layer is deposited on the surface of the substrate, and the metal M in the metal transition layer A One of Ti, Cr and Zr; A metal carbide layer, wherein the metal carbide layer is deposited on the surface of the metal transition layer, and the compound component of the metal carbide is M A C; A binary doping layer, wherein the binary doping layer is deposited on the surface of the metal carbide layer, and the compound composition of the binary doping layer is ta-C:M B / Si,M B It is one of Cu, Ag and Au.

2. The antistatic hard coating according to claim 1, characterized in that: The thickness of the metal transition layer is 0.1 to 0.2 μm.

3. The antistatic hard coating according to claim 1, characterized in that: The thickness of the metal carbide layer is 0.5 to 1 μm.

4. The antistatic hard coating according to claim 1, characterized in that: The thickness of the binary doped layer is 1 to 2 μm.

5. The antistatic hard coating according to claim 1 or 4, characterized in that: The binary doping layer has a C content of 80 to 90 at.%, a Si content of 10 to 20 at.%, and a M content of 1. B The content is 2 to 5 at.%.

6. The antistatic hard coating according to claim 1, characterized in that: The sp 3 The bond content is not less than 80%, the metal element M B It is dissolved in the ta-C structure in a free state.

7. A preparation method, characterized in that: The preparation method deposits and obtains the hard coating according to any one of claims 1 to 6, and the preparation method comprises loading a substrate into a reaction chamber; The reaction chamber is evacuated and heated, and the substrate is ion cleaned; Inert gas is introduced into the reaction chamber, a metal transition layer is deposited on the surface of the substrate, a metal carbide layer is deposited on the surface of the metal transition layer, and a binary doping layer is deposited on the surface of the metal carbide layer.

8. The preparation method according to claim 7, characterized in that: The metal transition layer is deposited by high power pulsed magnetron sputtering technology with a current density of 0.5 to 1 A / cm 2 , the bias voltage of the substrate is -100 to -150 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 5 to 10 min.

9. The preparation method according to claim 7, characterized in that: Metal carbide layers are deposited by high power pulsed magnetron sputtering with a current density of 1 to 1.5 A / cm on a graphite target. 2 , the current density of the metal target is 0.5 to 1A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 30 to 60 min.

10. The preparation method according to claim 7, characterized in that: When depositing the binary doped layers, the graphite target is sputtered by high power pulsed magnetron sputtering technology with a current density of 1 to 1.5 A / cm 2 The metal target and Si target were sputtered by bipolar pulsed magnetron sputtering technology. The current density of the metal target was 0.05 to 0.1 A / cm 2 , the current density of Si target is 0.2 to 0.4A / cm 2 , the bias voltage of the substrate is -50 to -100 V, the gas pressure in the reaction chamber is 0.2 to 0.5 Pa, and the deposition time is 60 to 120 min.